Encryption Of Speech Signal With Multiple Secret Keys - Dalila Slimani; Fatiha Merazka (Al-Lisaniyyat)
In this paper, we proposed an encryption system for speech signals based on circular shifts in row and column. This cryptosystem uses three secret keys. The original key is generated, randomly, using a pseudo noise sequence generator, and the two other keys are obtained by using the main key. The encryption system also uses Discrete Cosine Transform (DCT) or the Discrete Sine Transform (DST) to remove the signal intelligibility. Moreover, the performance of the proposed algorithm is also estimated by correlation coefficient quantity.